The Criminal Liability in the Context of Fertilizer Trade in Indonesia - Farida Luthfyana; Kuswardani, Kuswardani; Hussain, Mazlena Binti Mohammad; Hidaya, Wahab Aznul (JUSTISI, 2024)
Indonesia is an agricultural country and its agricultural sector which important in meeting food needs. On its journey, the agricultural sector in Indonesia is developing to improve the quality and production of food needs. Then, the fertilizer process has an important role in increasing the production of agricultural products, and the government needs to implement policies to subsidize the price of fertilizers for fertilizer distributors and arrange the regulations underlying the policy. If the fertilizer trade for fertilizer distributors is based on more than clear regulations, how can Indonesia's agricultural journey run. Thus, this study aims to attempt to describe the criminal liability of fertilizer trade based on court decisions at the first level up to the cassation level (namely, Decision Number. 137/pid.sus/2020/PN.Btg, Court of Appeal (Number. 487/Pid.Sus/2020/PT SMG and Cassation Decision Number. 78/Pid.Sus/2022). This study is normative research with a case approach, requiring secondary data in legal documents and references relevant to the subject matter. Data were collected by identification and inventory and then analyzed using the basic principles of criminal law. The novelty is fulfilling criminal liability is not enough regarding the psychological aspects (adult, healthy mind). However, it must also fulfill the normative measure of the act. The results showed that the defendant in the first instance and appellate level decisions were able to take liabilitybut was not sentenced because the element of the action in the prosecutor's charge, which stated "conducting trading business activities without having a license in the field of trade granted by the Ministry" was not fulfilled/proven, because the defendant had a trading business license (SIUP) issued by the Integrated Investment and Licensing Agency Number: 519/054/2014 dated June 04, 2014, under the name of the Agricultural Facilities and Organic Fertilizer Shop "Tani Jaya." The cassation verdict of the defendant can be held responsible and sentenced to punishment because measures from the psychological aspect are fulfilled. The measurements are from the normative aspect demanded by the public prosecutor, especially the elements that are also fulfilled. It can be consluded that based on the court's decision to measure the perpetrator's liability for a criminal offense, two measures must be met in imposing punishment.